The eye‐tracking computer device for communication in amyotrophic lateral sclerosis. (19th December 2013) - Spataro, R.; Ciriacono, M.; Manno, C.; La Bella, V.
<x xml:space="preserve">Abstract</x> Objective To explore the effectiveness of communication and the variables affecting the eye‐tracking computer system (ETCS) utilization in patients with late‐stage amyotrophic lateral sclerosis (ALS). Methods We performed a telephone survey on 30 patients with advanced non‐demented ALS that were provisioned an ECTS device. Median age at interview was 55 years (IQR = 48–62), with a relatively high education (13 years, IQR = 8–13). A one‐off interview was made and answers were later provided with the help of the caregiver. The interview included items about demographic and clinical variables affecting the daily ETCS utilization. Results The median time of ETCS device possession was 15 months (IQR = 9–20). The actual daily utilization was 300 min (IQR = 100–720), mainly for the communication with relatives/caregiver, internet surfing, e‐mailing, and social networking. 23.3% of patients with ALS (n = 7) had a low daily ETCS utilization; most reported causes were eye‐gaze tiredness and oculomotor dysfunction. Conclusions Eye‐tracking computer system is a valuable device for AAC in patients with ALS, and it can be operated with a good performance. The development of oculomotor impairment may limit its functional use.